Cryopreservation of Platelet Concentrates Under Moderately Low Temperatures (â€“70â€¦â€“80Â°C) with Preservatives Based on Combination of Cryoprotectants - Korobkova, Anna V.; Kompaniets, Antonina M. (Publishing House ‘Akademperiodyka’ of the National Academy of Sciences of Ukraine; Institute for Problems of Cryobiology and Cryomedicine, 2015)
N/A